The impact of the strategy of generating ideas on the achievement of science and science processes among first-grade students (Journal of the College of Basic Education, 2022)
This research aims to identify: - The impact of the strategy of generating ideas on the achievement of science and science processes for first grade intermediate students.The research community was selected from the intermediate schools of the Directorate of Education of Baghdad / Rusafa 3 for the academic year 2017/2018 AD. The research sample was intentionally chosen from the middle school of Imam Al-Hassan Al-Mujtaba () for boys, due to its proximity to the researcher's residence and the school administration's sincere desire to cooperate with the researcher. Of them (30) students in the experimental group and (30) students in the control group.